Teenage identity building in contemporary sociohistorical and cultural contexts - Gómez Palacio, Germán David; Carrasco Tapias, Nayib (Pensando Psicología, 2010)
Identity is a widely concept defined not only from psychology, but also from other sciences and disciplines.Historically, identity has been taken as an effect that “others” have on structuring personality. Nevertheless it’s necessary to discuss about the condition of that “other” who constitutes identity within the subject, according to which conditions it presents itself and until which point it’s interference arrives. Besides, but in the same constitutive way, science, the globalized world and generally new discourses have created different conditions for that “other” with the purpose that it presents itself with greater insistence, more determination and even more definitive over decisions taken by each subject. Subject today, especially the teenager, faces new and more specific and complex demands and, above all, more influent for developing his or her identity.
Keywords: culture; identity; other; subject